Determinants of Manufacturing Industry Agglomeration in Indonesia - Benny Imantria (Ekonomi dan Bisnis, 2025)
Purpose: This study aims to identify determinants of manufacturing industry agglomeration in Indonesia. Design/methodology/approach: Data used consists of 34 provinces over the period 2015-2023, which are analyzed using panel data regression with a fixed effect model. Findings: This study found that manufacturing industry agglomeration has different determinants in each region. Average years of schooling, road infrastructure, wage, and per capita income have a significant positive effect, labor force and labor productivity have a significant negative effect, while FDI has no significant effect on manufacturing industry agglomeration in Indonesia. Furthermore, this study also found that there are diseconomies of agglomeration where manufacturing firms begin to relocate and spread out from the agglomeration economic area. Research limitations/implications: This study only identifies the determinants of manufacturing industry agglomeration from the perspectives of production, distribution, and consumption. It has not yet addressed the diseconomies of agglomeration. Additionally, spatial analysis methods have not been used to determine the impact of economic agglomeration on neighboring provinces. Future studies could examine how technology, trade openness, migration, and institutions affect manufacturing industry agglomeration in Indonesia. Additionally, the threshold at which agglomeration leads to diseconomies also needs to be identified. Practical implications: In order to enhance labor absorption and labor productivity, policymakers are expected to increase the allocation of FDI to manufacturing industry and reduce skill mismatches. Furthermore, to attract private sector investment and create manufacturing industry agglomerations, the government needs to accelerate infrastructure development outside Java. Originality/value: Novelty of this study compared to previous studies lies in the independent variables representing production, distribution, and consumption activities. Paper Type: Research Paper Keywords: Agglomeration economies, Deindustrialization, Economic growth, Labor, Manufacturing industry.